Mutation of protease domain residues Lys37-39 in human protein C inhibits activation by the thrombomodulin-thrombin complex without affecting activation by free thrombin - Gerlitz, B; Grinnell, B W (The Journal of biological chemistry, 1996)
Activated protein C (aPC) is an important feedback regulator of the clotting cascade. In vivo, the conversion of protein C (PC) from its zymogen to activated form is mediated primarily by thrombin bound to thrombomodulin (TM), an endothelial cell surface protein. Molecular modeling suggests residues Lys37-Lys38-Lys39 of protein C's serine protease domain reside in a surface-exposed loop (variable region 1) whose high concentration of positive charge might be involved in protein-protein interactions. In this study, we have examined the role of the conserved tribasic Lys37-39 charge center in human protein C activation. This sequence was changed to acidic by substitution with Asp37-Glu38-Asp39 (DED) and Glu37-Glu38-Glu39 (EEE), or to neutrality by substitution with Gly37-Gly38-Gly39 (GGG). These mutant PCs, expressed and purified from recombinant human 293 cells, appeared normal with regard to intracellular processing, ability to be secreted, and formation of a viable active site for tripeptidyl-p-nitroanilide substrate cleavage. For activation by free thrombin, wild-type (wt) and mutant PCs displayed equivalent activation rates, as well as identical calcium-dependent inhibition of such activation. Activation of wt-PC with a soluble TM-thrombin complex yielded a 2,000-fold faster rate compared with that by free thrombin at the same (physiological) calcium level. In contrast, the acidic mutants DED and EEE exhibited virtually no TM-mediated increase in activation rate, while the neutral mutant GGG was somewhat intermediate with a 30-fold stimulation of activation rate. These reductions in activation rate were independent of the presence of chondroitin sulfate on TM. Our observations represent the first identification of residues whose mutation essentially uncouples activation by the TM-thrombin complex without affecting activation by free thrombin. Further, our results suggest that VR1 residues within the zymogen form of a serine protease can be important for recognition by physiological activators.